Everything all at once - Leno, Katrina (HarperTeen, an imprint of HarperCollinsPublishers, 2017)
When her struggles with anxiety worsen in the aftermath of a family death, Lottie is bequeathed a series of letters from her late aunt, a best-selling author, who leaves instructions to help Lottie overcome her fears and explore her own literary voice
Keywords: YOUNG ADULT FICTION / Books & Libraries / bisacsh; YOUNG ADULT FICTION / Epistolary (Letters & Diaries) / bisacsh; YOUNG ADULT FICTION / Family / Multigenerational / bisacsh; Anxiety / Fiction / sears; Aunts / Death / Fiction / sears; Letters / Fiction / sears; Authors / Fiction / sears; Secrets / Fiction / sears; Anxiety -- Juvenile fiction; Aunts -- Juvenile fiction; Authors -- Juvenile fiction; Letters -- Juvenile fiction; Secrets -- Juvenile fiction; YOUNG ADULT FICTION / Books & Libraries; YOUNG ADULT FICTION / Epistolary (Letters & Diaries); YOUNG ADULT FICTION / Family / Multigenerational; Anxiety; Aunts; Letters; Authors; Secrets; Tante; Lebensangst; Geheimnis; Autor; Brief; Jugendbuch